2008
DOI: 10.1111/j.1365-2958.2008.06262.x
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale transposon mutagenesis ofMycoplasma pulmonis

Abstract: SummaryTo obtain mutants for the study of the basic biology and pathogenic mechanisms of mycoplasmas, the insertion site of transposon Tn4001T was determined for 1700 members of a library of Mycoplasma pulmonis mutants. After evaluating several criteria for gene disruption, we concluded that 321 of the 782 protein coding regions were inactivated. The dispensable and essential genes of M. pulmonis were compared with those reported for Mycoplasma genitalium and Bacillus subtilis. Perhaps the most surprising resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(121 citation statements)
references
References 37 publications
5
111
1
4
Order By: Relevance
“…Several genome-scale identifications of such genes have been performed in prokaryotic and eukaryotic organisms by different groups with different strategies. Generally, there are three main experimental approaches to identify essential genes under particular growth conditions: massive transposon mutagenesis strategies (Judson and Mekalanos, 2000;Akerley et al, 2002;Salama et al, 2004;French et al, 2008), the use of antisense RNA (Ji et al, 2001;Forsyth et al, 2002) to inhibit gene expression, and the systematic inactivation of each individual gene present in a genome (Herring et al, 2003;Kobayashi et al, 2003). However, these results showed that percentage of essential genes in the whole genome is really low (Table 2).…”
Section: Experimental Gene Inactivation Approachmentioning
confidence: 39%
“…Several genome-scale identifications of such genes have been performed in prokaryotic and eukaryotic organisms by different groups with different strategies. Generally, there are three main experimental approaches to identify essential genes under particular growth conditions: massive transposon mutagenesis strategies (Judson and Mekalanos, 2000;Akerley et al, 2002;Salama et al, 2004;French et al, 2008), the use of antisense RNA (Ji et al, 2001;Forsyth et al, 2002) to inhibit gene expression, and the systematic inactivation of each individual gene present in a genome (Herring et al, 2003;Kobayashi et al, 2003). However, these results showed that percentage of essential genes in the whole genome is really low (Table 2).…”
Section: Experimental Gene Inactivation Approachmentioning
confidence: 39%
“…Cyclic di-AMP secreted into the cytosol of host cells by multiefflux pumps of the intracellular pathogen L. monocytogenes activates a cytosolic surveillance pathway in host immune cells such as macrophages (447). This potential role of c-di-AMP in virulence and stress resistance, in combination with the fact that genes coding for diadenylate cyclases are essential in intracellular pathogens (451)(452)(453)(454), makes c-di-AMP signaling pathways an attractive target for antimicrobial therapy.…”
Section: The Novel Cyclic Dinucleotide Second Messengers Cyclic Di-ammentioning
confidence: 99%
“…The 2 DGA and RHR motifs that are conserved in DacA proteins are also conserved in ssDacA. DacA orthologs appear to be essential for the viability of bacteria, as they cannot be deleted using traditional genetic techniques (Song et al, 2005;Glass et al, 2006;French et al, 2008;Woodward et al, 2010;Corrigan et al, 2011), and the significance of c-di-AMP in reported pathogens imply an important role of this protein in SS2 pathogenesis. In this study, we report this functional diadenylate cyclase (ssDacA) in SS2.…”
Section: Introductionmentioning
confidence: 99%